2014
DOI: 10.1371/journal.pone.0089181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physician-Nurse Substitution on Clinical Parameters: A Systematic Review and Meta-Analysis

Abstract: BackgroundPhysicians’ shortage in many countries and demands of high-quality and affordable care make physician-nurse substitution an appealing workforce strategy. The objective of this study is to conduct a systematic review and meta-analysis of randomised controlled trials (RCTs) assessing the impact of physician-nurse substitution in primary care on clinical parameters.MethodsWe systematically searched OVID Medline and Embase, The Cochrane Library and CINAHL, up to August 2012; selected peer-reviewed RCTs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 24 publications
(53 reference statements)
3
75
0
2
Order By: Relevance
“…A similar proportion has been found in Switzerland [6]. Furthermore, due to ageing populations, busy clinical workloads, and shortage of physicians in most healthcare systems, new approaches to hypertension care, involving pharmacists [7, 8] or nurses [9, 10], could be a promising approach to improve BP management and control.…”
Section: Introductionmentioning
confidence: 54%
“…A similar proportion has been found in Switzerland [6]. Furthermore, due to ageing populations, busy clinical workloads, and shortage of physicians in most healthcare systems, new approaches to hypertension care, involving pharmacists [7, 8] or nurses [9, 10], could be a promising approach to improve BP management and control.…”
Section: Introductionmentioning
confidence: 54%
“…A review assessed the impact on clinical outcomes of physician-nurse substitution in primary care, and included 11 randomised trials (Martínez-González 2014). Most studies were conducted in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…However, only five reviews reported adverse effects (Dudley 2011; Martínez-González 2014; Ngo 2013; Parker 2013; Wilson 2011), and one review did not find any studies reporting adverse effects (Van Lonkhuijzen 2012). Wilson 2011 reported undesirable effects on patient outcomes, and Dudley 2011 on access, coverage or utilisation, both with low- or very low-certainty evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Martinez-Gonzalez et al (2015) [1] identified twelve randomized controlled trials (RCTs) comprising 22, 617 patients specifically focussing upon the impact of shifting care traditionally delivered by physicians to nurse practitioners in primary care. Three quarters of these studies were conducted in Europe and nurse-led care was provided for patients with heart or lung disease, diabetes mellitus, digestive or skin disease, or infectious diseases.…”
Section: Discussionmentioning
confidence: 99%